KETIMPANGAN PENDIDIKAN DI INDONESIA: STUDI KEBIJAKAN DAN EVALUASI INOVASI UNTUK MENJEMBATANI PERBEDAAN KELAS SOSIAL - R Pugu, Melyana; Elmiwati, Elmiwati; Rukimin, Rukimin (CV. Lafadz Jaya, 2025)
Educational inequality in Indonesia remains a crucial issue that hinders the equitable distribution of human resources and national development. This study aims to identify the factors causing educational inequality and evaluate the effectiveness of policies and innovations implemented by the government to bridge social class differences. Using a literature review method, this study examines various literature, policy documents, and related research results. The findings reveal that educational inequality is influenced by economic and geographical disparities, the quality of educators, and access to educational facilities. Various policies such as the School Operational Assistance (BOS), the Indonesia Pintar Program (PIP), school zoning, and educational digitalisation have had positive impacts, but still face challenges in ensuring equitable access and quality. Cross-sectoral synergy, strengthening the implementation of affirmative policies, and sustainable innovation are needed to significantly reduce educational inequality in Indonesia.